Human resources management in the South African socio-economic context - Abbott, Penny (2012)
Ph.D. === The purpose of this study was to explore the lived reality of the work of Human Resource practitioners in South Africa in relation to the socio-economic context of their organisations and to consider how appropriate or not their responses might be to the impacts of that context on their work. This was explored through a qualitative study wherein interviews with 50 volunteer practitioners from all types of organisations spread across the country were conducted and compared to views of 17 informed commentators in this field. It was found that the work of Human Resource practitioners is signficantly impacted by social and economic factors external to the workplace, but that the current response by practitioners is probably not as appropriate as it could or should be. A role for human practitioners as “social activists” was identified and factors influencing whether such a role is played were explored. Frameworks of appropriate actions are proposed at both strategic and individual contributor level to support this role. The role of Human Resource professional bodies in addressing social issues in South Africa is challenged and a framework proposed to improve the extent to which leadership is given to Human Resource practitioners and to increase the visibility and voice of the profession in contributing to alleviation of societal problems. Recommendations for implementation of the proposed frameworks are proposed. One of the most significant recommendations is for Continuing Professional Development to provide coaching support based on Constructive-Developmental theory to enhance the ability of Human Resource practitioners to cope with the high levels of complexity that they encounter in their roles. Further research into a proposed model of influencing factors in the social activist role is recommended.